Literasi Media Digital Pada Anak-Anak Majelis Talim Hidayatul Mubtadiin - Asriyani Sagiyanto; Ferrari Lancia; Liliyana Liliyana; Achmad Syahlani (Jurnal Abdimas Komunikasi dan Bahasa, 2021)
Digital media literacy is “the ability to access, analyze, evaluate and communicate content from media messages. Digital media literacy also means the ability to understand, analyze, and deconstruct media imagery. The ability to do this is aimed at making viewers as consumers of mass media - including children become aware or literate about the way media is constructed / made and accessed. In short, this literacy is often called "media literacy". These community service partners are children of the recitation of the Hidayatul Mubtadiin Talim Council, located in Ciledug District, Peninggilan Utara Village, Tangerang City. The Talim Council has members consisting mostly of children from 7 years to 17 years of age. This partner has several problems including: First, many children of the talim council have received and consumed hoax news from the Whatsapp group and also social media. Second, the children of the talim assembly are less able to maintain their own privacy on social media, where there was once a case of children running away from their homes because they were friends with people they knew through their social media. The solution in this community service is by providing training on digital media literacy which can be achieved through things such as: a. how to filter good information from social media, b. how to process good information from social media, c. How to safeguard and protect personal data in a digital environment.